La redistribución del personal de un ayuntamiento a partir de la aplicación de un algoritmo Branch & Bound y del método de la esquina noroeste - Carmen Lozano Gutiérrez; Federico Fuentes Martín (Atlantic Review of Economics, 2014)
– Our research is aimed at finding the optimization of the service provided to citizens, in order to avoid breakdowns in certain administrative services compared to other services that have low levels of activity. The algorithm applied (Branch & Bound) detects what branches of the tree (administrative sections and services) are not optimal ones and have to be pruned for the purpose of not continue wasting resources and processes in cases that are far from the optimal solution. The application of Stepping Stone method or Nortwest Corner allow us to complete the staff reallocation within each administrative section based on timing optimization.
Keywords: C02; C63; M51; 330; branch and bound algorithm; personnel; work load optimization